2021
DOI: 10.1007/s12134-020-00800-2
|View full text |Cite|
|
Sign up to set email alerts
|

Fertility Intentions Within a 3-Year Time Frame: a Comparison Between Migrant and Native Italian Women

Abstract: The body of literature on the fertility of migrants in Europe has grown significantly in recent decades. The focus has mostly been on analysing their actual behaviours, and reflection on other crucial aspects extensively analysed in studies on natives has been lacking. In particular, differences between migrants’ reproductive decision-making process and that of natives are currently understudied in the European context. We will focus on the association between demographic and socio-economic characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…Notably, this study provided evidence that social and demographic factors, including migration did not influence fertility intentions of street youth in Kampala. This finding is in contrast with previous studies in which age, educational level, and marital status were associated with fertility intentions ( 38 , 39 ). Our previous study showed that despite the existence of many health care facilities in Kampala, access to SRH services among street youth were dismal.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, this study provided evidence that social and demographic factors, including migration did not influence fertility intentions of street youth in Kampala. This finding is in contrast with previous studies in which age, educational level, and marital status were associated with fertility intentions ( 38 , 39 ). Our previous study showed that despite the existence of many health care facilities in Kampala, access to SRH services among street youth were dismal.…”
Section: Discussioncontrasting
confidence: 99%
“…Kulu, 2005; Milewski, 2010). Migrants’ country of origin is considered a proxy of their values and cultural heritage that is likely to shape not only migrant fertility (Andersson & Scott, 2007; Bijwaard, 2010) but also migrants’ fertility intentions (De Valk, 2013; Mussino et al, 2021) and ideal family size (Mussino & Ortensi, 2018). The length of stay is one of the main determinants of reproductive behaviour, as it was shown that migrants’ fertility usually peaks right after migration and then tends to decrease as the duration of stay in the host country increases (Alderotti et al, 2019; Milewski, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on migrants’ fertility intentions has only been addressed in a small number of studies (e.g. Carlsson, 2018; Mussino et al, 2021). Most of these studies address very specific cases (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, the economic literature has attributed this development to the growth in career opportunities, the increasing relevance of the service sector, and the rise in female wages (Brewster and Rindfuss 2000). In addition, it has been shown that beliefs about the appropriate age for having children and the value attached to motherhood influence transitions to the first birth and that these attitudes vary by level of education, as well as by migration background (Mussino et al 2021).…”
Section: Trends In Family Formation In West Germanymentioning
confidence: 99%